Substance Use Disorder Treatment Outcomes: Methodological Overview of Metrics and Criteria - Marta Narváez‐Camargo; Oscar Lozano‐Rojas; Cinta Mancheño‐Velasco; Antonio Verdejo‐García (International Journal of Methods in Psychiatric Research)
ABSTRACT Aim The heterogeneous metrics and criteria used to assess the effectiveness of substance use disorders treatment hinders cross‐study comparisons. This review aims to parse such heterogeneity by analysing the operational definitions of variables used to derive metrics and outcome criteria, contributing to the standardisation process. Methods We conducted a systematic review in PubMed and PsycINFO between January 2000 and October 2023. We included published studies on substance use disorders that featured at least one of seven ‘a priori’ defined variables commonly used to obtain metrics and criteria for treatment effectiveness. The review process and reporting followed Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. Results Were identified three areas that can be used to define metrics and criteria associated with treatment outcome: as ‘substance use’ (abstinence and relapses), ‘treatment process’ (readmission, dropout, retention, and adherence) and ‘general wellbeing’ (quality of life). Operational definitions and metrics and criteria used were overall inconsistent. Conclusions The establishment of guidelines for evaluation of treatment outcomes is imperative, as heterogeneity is still present in the literature. We recommend that future trials provide outcomes metrics relevant to the identified categories, and that standardisation efforts continue toward harmonised criteria to report and interpret those metrics.